MANAJEMEN ORANG TUA DALAM PENDIDIKAN ANAK KELUARGA MUSLIM - Bahrun Ali Murtopo (AWLADY : Jurnal Pendidikan Anak, 2017)
All parents want their children to be those who worships. But in reality, unconsciously they actually treat children are not in accordance with their goals or even plunge to the opposite condition. Lots of parents are busy making a living. Aims to describe the role of parents in the education of Muslim families both parents busy in the village Wotbuwono, Kebumen, to describe the advantages and disadvantages that exist on the role of Muslim families Child Education. Every mother has the same obligation to provide appropriate education for their children. Its mean that mother became a housewife or a mother whose career has the same obligation to provide religious education and also educational value for children. Therefore, researcher tried researching on the management model of Islamic religious education in a Muslim family of four families that have different activities or classes. Begins from the desire of this fourth family that category of civil servants, seller man, peasants and the workers are making every effort to provide religious education for their children as a substitute for their absence during the activity through: follow TPQ / TPA, entrusted to neighbors and follow the educational institutions that provide servings more on the religious aspects such as: Playgroup, TK, MI and others. Keywords: Education, Children, Muslim FamilyASTRAKBahwa semua orang tua pasti  menginginkan agar anak-anak mereka menjadi orang yang shalih dan shalihah. Namun dalam kenyataannya, secara tidak sadar mereka justru memperlakukan anak-anak dengan cara yang menjauhkan dari terwujudnya cita-cita tersebut atau bahkan menjerumuskan kepada kondisi yang sebaliknya. Banyak sekali orang tua yang sibuk dalam mencari nafkah.Bertujuan untuk mendiskripsikan Pernan Oran Tua dalam Pendidikan keluarga Muslim yang kedua orang tuanya sibuk beraktifitas di Desa Wotbuwono, Kebumen, untuk mendiskripsikan kelebihan dan kekurangan yang ada pada perenan Pendidikan anak keluarga Muslim. Setiap Ibu memiliki kewajiban yang sama untuk memberikan pendidikan yang tepat untuk anaknya. Artinya Ibu menjadi ibu rumah tangga ataupun Ibu yang berkarir memiliki kewajiban yang sama untuk memberikan pendidikan agama dan juga pendidikan nilai bagi anak. Maka dari itu, peneliti berusaha meneliti tentang model manajemen pendidikan agama Islam dalam keluarga muslim 4 keluarga yang memiliki aktifitas berbeda atau kelas. Berangkat dari keinginan ini 4 keluarga yang berkata gori pegawai negeri sipil, pedagang, tani dan buruh tersebut melakukan berbagai upaya untuk memberikan pendidikan agama bagi anaknya sebagai pengganti ketiadaannya selama beraktifitas melalui: diikutkan TPQ/TPA dititipkan pada tetangga dan diamsukkan pada lembaga pendidikan yang memberikan porsi lebih pada aspek keagamaan seperti: Playgroup, TK, MI dan lain sebagainya.